Earning Management, Underpricing dan Pengukuran Kinerja Perusahaan yang Melakukan Kebijakan Initial Public Offering (IPO) di Indonesia - Bagyo, Yupono (Akutansi Bisnis & Manajemen ( ABM ), 2007)
Earning Management, underpricing and performance of company joining policy of IPO draw to be studied. Differ from research Husman (1996) to research phenomenon of underpricing of moment IPO, Nasirwan (2002) testing performance of pasca IPO, and Candy (2002) testing performance operate for and the finance performance, this research extend examination to phenomenon of earnings management, underpricing and company performance (finance, market) together. As much 31 company conducting IPO in Jakarta Stock Exchange in research of during period 1990 up to 2001, with unit analysis of during 6 years consisted of 3 years before IPO and 3 years after IPO, so that there is 186 unit analysis. Result of examination indicate that mean discretionary accrual is positive, what indication that company executing IPO of indication do policy of earnings management three years before IPO and three years after IPO by playing component accruals. But discretionary accrual before IPO and after IPO not differ, this matter indicate that company still continue policy of earnings management at least until three year after IPO. Furthermore examination to underpricing using initial return (Rt), proving that company executing IPO experience of underpricing on first when share traded in market sekunder. Mean of Initial return on first of trading in capital market is positive, even happened positive return until the third month a period of trading, after that happened degradation of return by the end of the year (December). Although there no difference which significant of performance of finance before and after IPO, result of examination prove that company executing IPO experience of degradation of performance of finance, whereas performance of market show there is difference of return [of] before IPO by return [is] first day [of] trading [in] Stock Exchange Market, and there is downhill tendency after IPO especially by the end of the year. If connected third the above phenomenon, in general the researcher cannot prove relation between policy earnings management, phenomenon underpricing, and the company market performance and finance performance conducting IPO.